Taxonomy and systematics of 2 new species of myxozoans (Cnidaria: Myxobolidae) parasitizing the gills of Iheringichthys labrosus (Teleostei: Pimelodidae) from southeastern Brazil - Diego Henrique Mirandola Dias Vieira; Maria João Santos; Sónia Rocha; Luis Filipe Rangel; Rodrigo Bravin Narciso; Reinaldo José da Silva (Parasitology)
Abstract